2017
DOI: 10.1016/j.jtho.2016.08.131
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Complete Resection of Thymoma by Minimally Invasive and Open Thymectomy: Analysis of an International Registry

Abstract: INTRODUCTION Minimally invasive thymectomy (MIT) is a surgical approach to thymectomy that has more favorable short-term outcomes than open thymectomy (OT) for myasthenia gravis. When performed for thymoma, the oncologic outcomes of MIT have not been rigorously evaluated. We analyzed determinants of complete (R0) resection among patients undergoing MIT and open thymectomy in a large international database. METHODS The retrospective database of the International Thymic Malignancy Interest Group (ITMIG) was qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 25 publications
2
54
0
1
Order By: Relevance
“…All of the studies were non-randomized and most were retrospective, so they were at higher risk of bias than a randomized-controlled trial (RCT). Several of the studies had a high risk of selection bias due to historical controls (24,32,34,36,37), differences in criteria for patient selection (22,33), or patient characteristic differences between groups (23). Studies that performed propensity score matching for outcomes of interest were considered at low risk for selection bias (25,(27)(28)(29)(30)35), as were the papers by Qian et al (31) and Ye et al (39), due to contemporary controls, the same selection criteria, and no differences in patient characteristics.…”
Section: Quality Of Evidence: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies were non-randomized and most were retrospective, so they were at higher risk of bias than a randomized-controlled trial (RCT). Several of the studies had a high risk of selection bias due to historical controls (24,32,34,36,37), differences in criteria for patient selection (22,33), or patient characteristic differences between groups (23). Studies that performed propensity score matching for outcomes of interest were considered at low risk for selection bias (25,(27)(28)(29)(30)35), as were the papers by Qian et al (31) and Ye et al (39), due to contemporary controls, the same selection criteria, and no differences in patient characteristics.…”
Section: Quality Of Evidence: Risk Of Biasmentioning
confidence: 99%
“…Five studies were assessed as having a high risk of reporting bias. The study by Burt et al (23) did not report data separately for the robotic group, except for an unmatched margin rate. In many studies (24,26,32,36), outcomes of interest were reported incompletely (e.g., missing a measure of variance), such that they could not be entered into the meta-analysis.…”
Section: Quality Of Evidence: Risk Of Biasmentioning
confidence: 99%
“…These results are consistent with those published by Wilshire and colleagues [12] who reported an R0 rate of 91% in their series of robotic thymectomy for 23 patients with thymomas larger than 3 cm (range 3 to 13 cm). In a recent analysis of the International Thymic Malignancies Interest Group registry data, Burt and colleagues [20] analyzed factors associated with R0 resection after thymectomy in 2053 thymoma patients. R0 resection rate after minimally invasive resection of thymoma was 94% in that study.…”
Section: Commentmentioning
confidence: 99%
“…Nowadays, little data with an adequate follow-up exists on oncological outcomes, nevertheless, the literature confirms the high rate (almost 90%) of complete R0 resections which is guaranteed both using the robotic system and open approach (8,9).…”
mentioning
confidence: 99%